2014
DOI: 10.1017/s0022215114000760
|View full text |Cite
|
Sign up to set email alerts
|

Otolaryngologist-performed head and neck ultrasound: outcomes and challenges in learning the technique

Abstract: Neck ultrasonography performed by an otolaryngologist is less accurate than that performed by an experienced radiologist, but is still a useful adjunct to clinical assessment, facilitating assessment in a 'one-stop' clinical setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…Most importantly, all otolaryngologists correctly diagnosed patient H, who had metastatic lymph nodes. An average diagnostic accuracy of 88% in our study is comparable to findings of the diagnostic accuracy of 83% obtained by a single US‐trained and dedicated otolaryngologist . However, there were large variations in diagnostic accuracy—ranging from 63% to 100%—among the otolaryngologists in our study.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Most importantly, all otolaryngologists correctly diagnosed patient H, who had metastatic lymph nodes. An average diagnostic accuracy of 88% in our study is comparable to findings of the diagnostic accuracy of 83% obtained by a single US‐trained and dedicated otolaryngologist . However, there were large variations in diagnostic accuracy—ranging from 63% to 100%—among the otolaryngologists in our study.…”
Section: Discussionsupporting
confidence: 80%
“…An average diagnostic accuracy of 88% in our study is comparable to findings of the diagnostic accuracy of 83% obtained by a single US-trained and dedicated otolaryngologist. 29 However, there were large variations in diagnostic accuracy-ranging from 63% to 100%-among the otolaryngologists in our study. A prior study also found individual variation in the diagnostic accuracy of surgeon-performed US in a trauma setting but attributed that to the differences in patient cases.…”
Section: Diagnostic Accuracy Of Surgeon-performed Hnusmentioning
confidence: 53%
See 1 more Smart Citation
“…1 It should be performed by experienced examiners to achieve the highest accuracy. 1,2 At our institution, all neck US examinations (including soft tissue evaluations) are performed and interpreted by radiologists, and not by US technicians. Currently, there is no consensus on whether or not the US results should be directly discussed between the radiologist and the patient at the time of the examination.…”
Section: Introductionmentioning
confidence: 99%
“…The examiner dependency [6] of sonographic findings highlights the need for practical experience and thus on-site training. Consequently, purely theoretical training does not seem to be sufficient in the context of education.…”
Section: Introductionmentioning
confidence: 99%